Między konfliktem a pojednaniem. Ludy rdzenne Meksyku w ustawie zasadniczej i działalności administracyjnej publicznej - Biernacka, Maja (Polityka i Społeczeństwo, 2020)
The article is dedicated to constitutional grounds and public policy in Mexico with reference to indigenous peoples. Many of them are subject to severe social problems such as school absenteeism and dropouts, illiteracy, poverty and unemployment. The fundamental institution which specializes in public activity for the benefit of indigenous people in Mexico is the National Commission for the Development of Indigenous Peoples (La Comisión Nacional para el Desarrollo de los Pueblos Indígenas). It was founded under Article 2 of the Constitution and operates at the federal level to devise strategies and implement public sector activities, including entitlement programs in order to foment their development.